Sputum smear conversion rate of adult pulmonary tuberculosis patients under directly observed treatment shortcourse in Rajarajeswari Medical College and Hospital, Bangalore - Basavaraju, Vidya; Bukanakere, Chetan Lakshmikantha; Nagaraj, Damayanthi M.; Manjunatha, Shashikala (International Journal Of Community Medicine And Public Health, 2019)
Background: Tuberculosis is among the most important causes of death from a single infectious agent and a major public health problem causing an enormous burden of disease and economic impact especially in the developing countries. Pulmonary tuberculosis is the most common form of tuberculosis causing >85% of all tuberculosis cases. The smear conversion rate is an operational indicator for the directly observed treatment short course (DOTS) strategy of Revised National Tuberculosis Control Programme (RNTCP) in India. Methods: A longitudinal study was conducted in DMC, RRMCH, in the first two quarters of the year 2013 i.e., from January 1st to June 31st of the year 2013. All 130 adult category I (new) sputum smear positive cases that attended DMC, and registered under RNTCP constituted the sample for the study. Data was collected by interview method by using pre-tested, semi-structured questionnaire. Data was analyzed using SPSS version 20.0. Results: Majority of the study subjects was >50 years, Hindus, illiterates, belonged to nuclear family from rural area belonged to upper lower socio-economic class. The overall sputum smear conversion rate is 92.4%. Lower sputum smear conversion rate was observed in the following risk factors like the male gender, smoking, diabetes, initial high pre-treatment smear grading and poor drug compliance. Conclusions: The overall sputum conversion rate at the end of two months of intensive phase under (DOTS) chemotherapy in 118 sputum smear positive (cat I) new pulmonary tuberculosis patients in Designated Microscopy and Treatment Centre (DMC) Rajarajeswari Medical College and Hospital was 92.4%.